Oxidation and viability of Vanilla phaeantha explants exposed to ethylene during in vitro cultivation - Feitor Carvalho, Taciany; Gomes dos Reis Pereira, Lislie; Scalco Oliveira, Esthéfany; dos Santos Ambrósio, Alexandra; Rodrigues da Cunha Neto, Antonio; Taniguchi, Marisa; Valquíria dos Reis, Michele; Régis Santos, Breno (Revista Brasileira de Engenharia de Biossistemas, 2025)
Vanilla phaeantha is a native species of Brazil with great potential for both the fragrance industry and ornamental cultivation. However, the propagation of this orchid through traditional methods is limited, making in vitro micropropagation a promising alternative. This study aims to evaluate the in vitro micropropagation of Vanilla phaeantha, with a focus on the effects of exogenous ethylene application on the viability and development of leaf and root explants. This research was carried out in June 2024, utilizing explants obtained from plants grown in the Federal University of Lavras' Botanical Garden. The explants underwent a disinfection process and were inoculated in Murashige and Skoog (MS) medium, supplemented with different ethylene concentrations (0, 15, 20, 25, and 30 ppm). The explants were cultivated under controlled temperature and continuous light. The results showed that, regardless of the explant type or ethylene concentration, all explants exhibited complete oxidation, with no callus formation, shoots, or roots. This suggests that the MS medium, although suitable for many plant species, may not be ideal for Vanilla phaeantha without modifications, such as the addition of antioxidants or other growth regulators. The study indicates that ethylene may not be beneficial for the in vitro propagation of Vanilla phaeantha, as its exogenous application seems to induce oxidative stress, hindering the regeneration of plant structures. In conclusion, further research is needed to optimize in vitro culture conditions, possibly focusing on alternative hormonal treatments and adjustments to the culture medium to improve the propagation success of this orchid species.